The influence of attitude, rewards, training and working environment on employees’ performance / Noor Malinjasari Ali...[et al.] - Ali, Noor Malinjasari; Abd Kadir, Nik Nur Aida; Mohamed Nor, Raslina; Kamaruddin, Kardina; Borhanuddin, Rahayu Izwani (Universiti Teknologi MARA, Cawangan Melaka, 2019)
This paper attempts to understand employee’s performance in the Malaysian public sector. There are two objectives of the study. Firstly, is to examine the influence of training, reward, attitude and working environment on employees’ performance; and secondly, to identify the most significant factor (training, reward, attitude, and working environment) that influences employees’ performance. This study examined the factors that influence employees’ performance at a government office in Kelantan. Using convenience sampling and self-administered questionnaires, data from 85 employees were analyzed using Pearson Correlation and Multiple Regression Analysis. The results indicated that out of four variables that had been chosen, only training influences employees’ performance. The study recommended for a bigger sample size. The study also suggested using longitudinal study for future research. Another suggestion is to use qualitative study with in depth interviews to gauge better understanding between variables.